REUSE OF THE LEFTOVER PERMEATEWATERAND OF WASTEFROM A REVERSE OSMOSIS WATER TREATMENT CENTRAL OF A HEMODIALYSIS HOSPITAL UNIT - Ribeiro, L.; Sanches-Pagliarussi, M.; Ribeiro, J. (Revista Brasileira de Engenharia de Biossistemas, 2016)
This paper delas with the possibility of reusing water from the waste and the left over water permeated from a Reverse Osmosis system or, of hemodialysis unit of the Hospital das Clínicas de Ribeirão Preto (HCRP-USP). The study was carried out by structural survey with physical plants and layout of the place,making visits to this place to analyze the quality and check the amount of water used in the same and especially the study of bacteriological and physical-chemistry characteristics the water to be reused. The result of the analysis of left over permeated water and wastes howed that it is possible to reuse the left over permeated water directly in to the HCRP-USP central box, sincethis does not change the quality of the hospital's water supply, only being 0.73% dilution. With the installation of water recycling to spare system permeated the HCRP-USP started to have na economy in water volume of 575 m3/month. The total cost of system implementation was R$ 5,809.43, that is, with very little financial resources the hospital obtained a great savings in input water.